Communication—Microscopic View of the Ethylene Carbonate Based Lithium-Ion Battery Electrolyte by X-ray Scattering. Issue 2 (4th January 2019) - Feng, Zhange; Sarnello, Erik; Li, Tao; Cheng, Lei
Abstract : Small angle X-ray scattering studies are conducted to gain insight of the microscopic structures on LiPF6 /carbonates battery electrolyte. The result shows that ethylene carbonate (EC), with a cyclic structure, forms nanoclusters of ∼ 1 nm in linear carbonates ethyl methyl carbonate (EMC), diethyl carbonate (DEC), while it fully dissolves in a cyclic carbonate, propylene carbonate (PC). The ion pair of LiPF6 in carbonates is measured to be ∼ 6 Å in dimension, corresponding to the form of contact ion pair. The new microscopic structure the battery electrolyte reported herein is important for the understanding of non-ideal behavior of LiPF6 carbonate based electrolyte and thus the design of new electrolyte.